Phytoremediation of Catfish (Clarias gariepinus) Aquaculture Waste Using Giant Salvinia (Salvinia molesta) And Water Lettuce (Pistia stratiotes) - Linda Wulandari; Ibi Fatimah; Turwuri Handayani; Yulintine Yulintine; Maryani Maryani (Jurnal Akuakultur SEBATIN, 2023)
This research was conducted with the aim of knowing the ability of giant salvinia (Salvinia molesta) and water lettuce (Pistia stratiotes) aquatic plants to improve the quality of catfish (Clarias gariepinus) aquaculture wastewater with parameters of temperature, acidity (pH), dissolved oxygen (DO), ammonia and organic matter. This research was conducted for 20 days and used a Randomized Block Design (RBD), with observation and sampling time on days: 0, 5, 10, 15, and 20, treatment K as control (without aquatic plants), giant salvinia (KI)) and water lettuce (KA). The results showed that the phytoremediation process using aquatic plants, water lettuce, and giant salvinia, had a significant effect on improving the quality of wastewater from catfish aquaculture waste. Water lettuce was able to reduce ammonia levels by 97.81% and organic matter by 33.19%, while giant salvinia was able to reduce ammonia levels by 97.23% and organic matter by 20.00%. This shows that in improving the quality of catfish aquaculture waste, water lettuce (Pistia stratiotes) is more effective than giant salvinia.